‘Paradise by the Dashboard Light’: Working with a Simple PDCA Cycle at Avans University of Applied Sciences - Simons, Ellen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The intention of this paper is to share some of our experiences with implementing a simple ‘Plan Do Check Act’ (PDCA) cycle within our Learning and Innovation Centre (LIC). The PDCA-cycle is a never ending cycle designed to improve quality and efficiency. The PDCA as developed within LIC is not something completely new or innovative. But making use of the PDCA cycle enables us to link processes in a more effective way than before. In the current times of budget cuts the outcomes proved to be very useful. The paper is divided in three parts. First some basic background information is given about Avans University. Secondly the implementation of the PDCA cycle is described in more detail with a special focus on the planning and checking elements of the PDCA cycle. Finally, some users are quoted who judge the PDCA cycle. Some recommendations based on two years’ experience are given at the end of this paper.